EFFICACY IN ASSESSING THE NUTRITIONAL AND BIOLOGICAL VALUE OF GINGER GELATIN CAPSULES IN PATIENTS WITH COVID-19 - Guli I. Shaykhova; Bobomurod B. Ortikov; Doniyor B. Mirazimov (Central Asian Journal of Medicine, 2022)
The purpose of the study: To study the nutritional, biological value and effectiveness of a new food supplement of ginger in a gelatin shell in patients with COVID-19. Research methods and materials. A new ginger food product in a hard gelatin shell, developed by SHANAZ LLC; coronovirus patients, case histories. Results: ginger in a gelatin capsule, developed in collaboration with SHANAZ LLC (Uzbekistan), which contains sufficient nutrients, minerals, vitamins and dietary fibers. The study of effectiveness in patients with COVID-19 showed a decrease in body weight, ensuring the function of the digestive organs, the exclusion of metabolic products, and the normalization of metabolic processes. Conclusion. Ginger in a gelatin capsule contains proteins (g) 1.8±0.104, fats (g) 0.8±0.076, carbohydrates (g) 15.8±0.55; dietary fiber (g) 2±0.275, total calorie (kcal) - 80±1.445. The composition contains vitamins and mineral elements that play a primary and secondary role in strengthening the immune system.